Process Evaluation of a Promotora de Salud Intervention for Improving Hypertension Outcomes for Latinos Living in a Rural U.S.–Mexico Border Region. Issue 3 (May 2014) - Sánchez, Victoria; Cacari Stone, Lisa; Moffett, Maurice L.; Nguyen, PhoungGiang; Muhammad, Michael; Bruna-Lewis, Sean; Urias-Chauvin, Rita
Hypertension is a growing public health problem for U.S.–Mexico border Latinos, who commonly experience low levels of awareness, treatment, and control. We report on a process evaluation that assessed the delivery of Corazón por la Vida, a 9-week promotora de salud –led curriculum to help Latinos manage and reduce hypertension risks in two rural/frontier counties in the New Mexico border region. Ninety-six adults participated in the program, delivered in three waves and in three communities. We assessed program delivery and quality, adherence, exposure, and participant responsiveness. Participant outcome measures included self-reported eating and physical activities and assessment of community resources. Findings suggest that the program was fully delivered (99%) and that most participants (81.7%) were very satisfied with the educational sessions. The average participant attendance for educational sessions was 77.47%. We found significant differences in self-reported behavioral changes depending on the number of sessions completed: The higher the dose of sessions, the better the self-reported outcomes. These findings suggest that a promotora-led curriculum may be useful for promoting self-management of chronic disease in rural/frontier border Latino populations. Future evaluation should focus on training and implementation adaptations within evidence-based chronic disease programs for diverse Latino communities.